Environmental Assessment of Used Lubricant Oil in Southern Brazilian Region - Tsambe, Malaquias Zildo António; Almeida, Cássio Florisbal de; Ugaya, Cássia Maria Lie; Cybis, Luiz Fernando de Abreu (Journal of Environmental Accounting and Management, 2026)
Brazil is currently the sixth world largest lubricating oil consumer, as a result, the sixth largest used lubricating oil (ULO) producer, with an annual ULO production of about one million liters. Therefore, due to the environmental consequences and also to the large amount of this waste, it becomes necessary to quantify and qualify the impacts resulting from ULO management process. The study evaluates, through the life cycle assessment (LCA) methodology, the current ULO management system in southern Brazil. Two comparisons regarding the environmental performance scenarios were defined with the use of eight impact categories: land use, nonrenewable energy, global warming potential, aquatic acidification potential, aquatic eutrophication potential, human toxicity potential, terrestrial ecotoxicity potential and carcinogens potential. The LCA was conducted based on Simapro, using the “IMPACT 2002+ for ULO v2.12/IMPACT 2002+” method. The scenarios comprised the two ULO management models currently used in Brazil. The first, which is designated in the study, by TTR scenario and the second, regarded as TsTR scenario. The LCA results showed that the re-refine phase, in the TsTR scenario, presents lower impact when compared to the corresponding TTR scenario phase. The TsTR scenario presented the greatest impacts in seven categories (carcinogens, terrestrial ecotoxicity, land use, eutrophication, globalwarming, use of nonrenewable energy and acidification), corresponding to about 87.5% of all the impacts. On the contrary, the TTR scenario presented lower impacts in these seven categories, impacting more on only one category (human toxicity). In relation to transportation, the opposite occurs, transport in the TTR scenario presents a larger contribution, impacting 100% more than transport in the TsTR scenario. The presence of the transshipment center decreases the amount of re-refining impacts in 87.5% of the categories in the TTR scenario. Transport in the TTR scenario contributes relatively more to the fact that the collecting vehicles cover a larger average distance (789km) when compared to transport in the TsTR scenario, where the vehicles cover a smaller average distance (629.44km). The study allowed to conclude, through the LCA methodology, that the ULO life cycle with TTR type scenario causes lower impacts on the natural environment than a cycle with a TsTR type scenario.